Access to Information is the Basis of a Democratic System and Good Governance - Kessal, Abdelouahab (Journal of Legal Studies and Researches, 2021)
This study attempts to address the right to access information as a fundamental freedom, and its role in reinforcement the values of democracy and good governance, in order to achieve the objectives and principles contained in most human rights conventions. By addressing the standards governing the embodiment of this right, and how it contributes to the values of democracy and good governance, whose manifestations appear to enshrine freedom of expression, the principle of transparency in the work of state institutions and the fight against manifestations of corruption.